The effect of teaching the writing process in the development of the writing skill in students of English composition II course of the English teaching major at the Foreing Language Department at the University of El Salvador, semester I-2018 - Carrillo González, Yaqueline Lissette
This project was focus on the writing process taught by composition II instructors and its effectiveness in students’ writing skill. The main purpose was to know if learners followed or not the writing process in their papers, notes and any kind of paragraphs they could provide related with the subject. It is important to define the concept of writing and the process that a good writer must follow in order to create academic and professional pieces of writing. According to Brown (2001, p. 336) writing is a thinking process; a writer produces a final written product based on their thinking after the writer goes through the thinking process. Based on the previous definition writing is not just write whatever comes to the mind, it needs thinking, analysis and organization. Writing is a very active process which needs too much attention in order to get an efficient final product. In brief, this research will help to identify the main problems students present in their papers, also, if it is difficult for them to understand and follow the writing process, beside, teachers and students’ opinions about the strategies implemented to improve this skill through the writing process.